″The issue of the acquisition of civil competence by gifted and capable school students″ - Tkachоv, A. S. (Problems of Engineer-Pedagogical Education, 2018)
The article defines the specifics of civil competence development in gifted and capable adolescent students. On the basis of the analysis of scientific literature, the paper specifies the author‟s interpretation of the concept of “civil competence” as an integrative personal quality that manifests itself in the awareness of the functioning of the Ukrainian state and its problems, in the ability to implement a complex of civil rights, liberties and responsibilities in a democratic civil society, in the willingness to take an active part in ensuring its further development. It has been ascertained that this competence combines relevant knowledge, skills, values, and basic human qualities. It has been proved that the problem of developing civil competence becomes especially important while working with gifted and capable adolescents who, given properly organized pedagogical support, have all the opportunities in the future to become part of the national elite. The article analyzes practical experience of the complex development of civil competence among school students of the above-mentioned category during the lessons (social science lessons in particular) as well as during some extracurricular activities of the adolescents.